Epigenetics and a new look on metabolic syndrome - Kuneš, J; Vaněčková, I; Mikulášková, B; Behuliak, M; Maletínská, L; Zicha, J (Physiological research, 2015)
The incidence of metabolic syndrome increases in the developed countries, therefore biomedical research is focused on the understanding of its etiology. The study of exact mechanisms is very complicated because both genetic and environmental factors contribute to this complex disease. The ability of environmental factors to promote phenotype changes by epigenetic DNA modifications (i.e. DNA methylation, histone modifications) was demonstrated to play an important role in the development and predisposition to particular symptoms of metabolic syndrome. There is no doubt that the early life, such as the fetal and perinatal periods, is critical for metabolic syndrome development and therefore critical for prevention of this disease. Moreover, these changes are visible not only in individuals exposed to environmental factors but also in the subsequent progeny for multiple generations and this phenomenon is called transgenerational inheritance. The knowledge of molecular mechanisms, by which early minor environmental stimuli modify the expression of genetic information, might be the desired key for the understanding of mechanisms leading to the change of phenotype in adulthood. This review provides a short overview of metabolic syndrome epigenetics.
Keywords: Animals; Metabolic Syndrome; epigeneze genetická; lidé; zvířata; typy dědičnosti; Disease Susceptibility; Inheritance Patterns; metabolický syndrom; Epigenesis, Genetic; náchylnost k nemoci; Humans